Research on the sustainable development of agricultural product supply chain in three northeast provinces in China - Fan, Xuemei; Zhang, Yingdan; Ma, Yuanhang; Zhao, Cong; Liang, Buxin; Chu, Hao (Frontiers in Public Health, 2023)
Background The sustainable development of the agricultural product supply chain (APSC) is the key to protecting public health. Methods This paper explores the sustainable development status of the APSC in three northeast provinces of China from 2007 to 2020 and the development trend in the next 5 years by using the entropy weight—matter-element extension model (MEEM) and autoregressive integrated moving average model (ARIMA), taking into account the background of relatively backward development and the high proportion of agricultural output in these three provinces. Results According to the research results, the sustainable development of the APSC in Jilin Province is relatively stable, Heilongjiang Province has made considerable progress in the sustainable development of the APSC in recent years, while Liaoning Province has shown a significant downward trend in recent years in the sustainable development of the APSC, despite a strong development momentum in previous years. Conclusions The findings of this paper can be applied to the governance of APSC in other rural areas with uneven development. The assessment also provides guidance on the quality and safety of agricultural products and public health, and raises the awareness of policymakers on the importance of the APSC.